Bilateral agreement for academic years 2008/2013 Socrates programme: higher education (Erasmus) between Universidade Lusíada de Lisboa and Università degli Studi Mediterranea di Reggio Calabria - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within LLP (Lifelong Learning Programme)/Erasmus. - Subject area: Architecture.